2010
DOI: 10.1016/j.jala.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Micropumping by an Acoustically Excited Oscillating Bubble for Automated Implantable Microfluidic Devices

Abstract: W hen a gaseous bubble in liquid is excited by acoustic waves, it oscillates (expands and shrinks) at the wave frequencies and generates strong vortical flows around it, the so-called cavitational microstreaming. This article describes the development of a micropumping principle using cavitational microstreaming. The key idea is to place a capillary tube vertically above an oscillating bubble to collect the upward microstreaming flow. When the bubble is excited at its resonance frequency, it oscillates with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…They are greatly beneficial in a number of proposed applications in chemical, biological, and physical processes such as mixing, [149][150][151] pumping, 152,153 characterizing enzymatic reactions, 154 cell lysis, 155 and sorting and enrichment. 156,157 A thorough review article on applications of oscillating microbubbles in microfluidics is recently written by Hashmi et al 158 Although, there are a number of techniques to generate bubbles in microfluidic channels, 159,160 using a cavity is found to be the simplest.…”
Section: A Cavitation Microstreamingmentioning
confidence: 99%
“…They are greatly beneficial in a number of proposed applications in chemical, biological, and physical processes such as mixing, [149][150][151] pumping, 152,153 characterizing enzymatic reactions, 154 cell lysis, 155 and sorting and enrichment. 156,157 A thorough review article on applications of oscillating microbubbles in microfluidics is recently written by Hashmi et al 158 Although, there are a number of techniques to generate bubbles in microfluidic channels, 159,160 using a cavity is found to be the simplest.…”
Section: A Cavitation Microstreamingmentioning
confidence: 99%
“…In particular, as the frequency of the acoustic wave gets close to the resonance frequency of bubble column, the oscillation amplitude of the bubble become maximized (resonated). In this case, the fast and strong interface oscillation at the open tip of the cylinder generates a quasi-steady streaming flow (arrows in Figure 1) [3,4]. In turn, this streaming flow changes the mechanical stresses on the oscillating interface surface, eventually producing a net force exerted on the propulsion system.…”
Section: Propulsion Conceptmentioning
confidence: 99%
“…The side view shows the dimension of the open tip in the cylinder. The dimension is 80 × 45 × 530 µm3 . The arrayed unit has 10 cylinders that are parallel to each other.…”
mentioning
confidence: 99%
“…The bubble's oscillations produced jet-like propulsion as fluid was expelled from the tube normal to the interface when the bubble expanded and pulled in symmetrically when it retracted. More recently, Ryu et al reported on a technique for micropumping using an acoustically excited oscillating bubble for implantable microfluidic devices (Ryu et al 2010).…”
Section: Introductionmentioning
confidence: 99%